Postępowanie w sprawie odpowiedzialności konstytucyjnej prezydenta Chorwacji - Grabowska, Sabina (Polityka i Społeczeństwo, 2020)
The subject of this study is the Croatian procedural regulations concerning the constitutional responsibility of the president. I try to answer the question of whether the Croatian legislator normalized the functioning of the institution in an appropriate manner.